Marketing in the moment : the practical guide to using Web 3.0 marketing to reach your customers first - Tasner, Michael Scott, 1984- (FT Press, 2010)
Provides tips and advice on Web 3.0 marketing, describing ways to use the Internet, mobile devices, and social media to improve sales, traffic, market share, and profits.